Go digital of PAMMA Herba through rebranding and digital marketing - Anang Sujoko; Eko Widodo; Muhammad Firdaus; Noer Rahmi Ardiarini; Zulfaidah Penata Gama; Dicky Wahyudi (Journal of Community Service and Empowerment, 2024)
PAMMA (Panti Asuhan Muhammadiyah Malang) has a home industry product in the form of rhizome beverages. The beverage products from PAMMA were developed by the Doktor Mengabdi program for Brawijaya University and has survived until now. The problem is, the previous Doktor Mengabdi program still focused on the beverage production process, and PAMMA still markets its products conventionally, even though the industrial era has penetrated the digital market (e-commerce). This community service program aims to maintain of the rhizome beverage industry from PAMMA by conducting packaging rebranding and digital marketing, so that PAMMA products can go to the digital market (Go Digital). Implementation methods include: First, assistance with the legalization and re-branding of 5 rhizome beverage products. Second, a digital marketing workshop for rhizome beverage products for PAMMA residents. The results of this community program are measured by the legalization of NIB PAMMA Herba, and changes to the packaging design of 5 PAMMA rhizome beverage products. Digital marketing training provides results in the form of a shop on an e-commerce platform for PAMMA which can be used to sell its rhizome products, optimize advertising in new media by adjusting its target market, and expand marketing by utilizing digital media. The target is that with a schematic and sustainable program, it can increase economic income and maintain the sustainability of the home industry of rhizome beverage products from PAMMA.